2022
DOI: 10.1111/1440-1630.12793
|View full text |Cite
|
Sign up to set email alerts
|

‘Learning in and out of lockdown’: A comparison of two groups of undergraduate occupational therapy students' engagement in online‐only and blended education approaches during the COVID‐19 pandemic

Abstract: Introduction In many countries, the COVID‐19 pandemic resulted in sudden changes to the delivery of health professions education in response to local and national lockdowns. Within occupational therapy, university education programs traditionally delivered in face‐to‐face classroom, and clinical settings, the transition to online learning presented unique issues and challenges for faculty and students. This study compared the experiences and perceptions of learning in two groups of occupational th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…This is consistent with students reporting that the switch to online/remote learning during the pandemic improved their academic performance both by aiding in the development of digital competencies and by helping them to better organize daily time and activities (Mamutovic, 2021). Students also reported that they received more individual support from instructors when taking online courses during the pandemic (Brown et al , 2022). Performance improvements from online instruction also mimic what has happened in the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with students reporting that the switch to online/remote learning during the pandemic improved their academic performance both by aiding in the development of digital competencies and by helping them to better organize daily time and activities (Mamutovic, 2021). Students also reported that they received more individual support from instructors when taking online courses during the pandemic (Brown et al , 2022). Performance improvements from online instruction also mimic what has happened in the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos de este estudio, al igual que los presentados por Klug & Peralta (2019) y Mayor Paredes (2020), indican que las tutorías virtuales sincrónicas aportan de manera integral en la formación profesional, ya que colaboran en la articulación de aspectos teóricos-prácticos y fomentan el desarrolle de habilidades actitudinales de los/as estudiantes. En concordancia con lo planteado por Castellanos Ramírez & Niño Carrasco (2020) y Brown et al (2022), los hallazgos expuestos relevan que las tutorías virtuales sincrónicas favorecen el aprendizaje, al ser un espacio participativo que permite compartir las experiencias, favorecer el apoyo mutuo entre docentes y estudiantes, y a manejar los aspectos emocionales involucrados en la práctica. Para algunos/as participantes, las tutorías virtuales promueven valores como la solidaridad y la empatía entre compañeros/as (Valderrama Núñez et al, 2021), y permiten el reconocimiento de sí mismos/as como seres sociales e interdependientes en su proceso formativo (Valderrama Núñez, 2020).…”
Section: Tensiones Sobre El Aporte De Las Tutorías Al Aprendizajeunclassified
“…Much of the literature published to date focuses on the impact on students of the sudden switch to COVID-safe teaching arrangements, which were generally of limited duration (6,(12)(13)(14)(15)(16)(17)(18)(19)(20) or focused on specific responses to eLearning (21,22) with medicine most represented. Very little of the literature has been empirical in nature (17).…”
Section: Introduction and Contextmentioning
confidence: 99%
“…Blended approaches to teaching and learning (e.g., online lectures with practical in-class teaching), have been common in health professional education in the previous decade ( 6 ). The COVID-19 interruptions, however, required virtual delivery of all teaching, including practical skill-based content, simulations, and fieldwork placements.…”
Section: Introduction and Contextmentioning
confidence: 99%